Early Lupus Project – A multicentre Italian study on systemic lupus erythematosus of recent onset. (October 2015) - Sebastiani, G D; Prevete, I; Piga, M; Iuliano, A; Bettio, S; Bortoluzzi, A; Coladonato, L; Tani, C; Spinelli, F R; Fineschi, I; Mathieu, A
Background: Systemic lupus erythematosus (SLE) is an autoimmune disease with a high degree of variability at onset that is problematic for a correct and prompt diagnosis. We undertook this project with the purpose of collecting an inception cohort of Italian patients with recent-onset SLE, in order to obtain information on the main clinical and serological characteristics at the beginning of the disease. In this first report we describe the characteristics of this cohort at study entry. Methods: All patients with a diagnosis of SLE (1997 ACR criteria) and a disease duration less than 12 months were consecutively enrolled between 1 January 2012 and 31 December 2013 in a multicentre prospective study. Information on clinical and serological characteristics at study entry and then every six months was collected into a specific electronic database. Statistical analysis was performed by means of the Openstat program. Results: Among 122 patients enrolled (103 F) 94.3% were Caucasians. Mean age (SD) of patients at study entry was 37.3 (14.3) years, mean age at disease onset was 34.8 (14.3) years, mean age at diagnosis was 36.9 (14.3) years, and mean disease duration was 2.9 (3.9) months. The frequency of the manifestations included in the 1997 ACR criteria was as follows: ANA 97.5%, immunologic disorders (anti-dsDNA, anti-Sm, antiphospholipid antibodies) 85.2%, arthritis 61.8%, haematologic disorders 55.7%, malar rash 31.1%, photosensitivity 29.5%, serositis 27%, renal disorders 27%, oral/nasal ulcers 11.5%, neurologic disorders 8.2%, and discoid rash 5.7%. The cumulative frequency of mucocutaneous symptoms was 77.8%. At enrolment, autoantibody frequency was: ANA 100%, anti-dsDNA 83.6%, anti-SSA 28%, anticardiolipin 24.5%, anti-nRNP 20.4%, anti-beta2GPI 17.2%, lupus anticoagulant 16.3%, anti-Sm 16%, and anti-SSB 13.1%. Conclusions: In this paper we describe the main clinical and serological characteristics of an Italian inception cohort of patients with recent-onset SLE. At disease onset, mucocutaneous manifestations, arthritis and haematologic manifestations were the most frequent symptoms; ANA, anti-dsDNA and complement reduction were the most frequent laboratory findings. Our data confirm that the diagnosis of SLE is a challenging one, and that SLE is a severe disease even at onset, since the majority of patients require at least a hospitalization before the diagnosis.